Innate signals compensate for the absence of PKC-{theta} during in vivo CD8(+) T cell effector and memory responses. - Marsland, B; Nembrini, C; Schmitz, N; Abel, B; Krautwald, S; Bachmann, M; Kopf, M (2005)
PKC- is central to T-helper (Th) 2 cell differentiation and effector function; however, its importance for antiviral effector, and in particular memory CD8(+) T cell responses, remains unclear. We have investigated the role of PKC- during in vivo and in vitro responses against influenza virus, lymphocytic choriomeningitis virus, vaccinia virus, and replication-deficient virus-like particles. In the absence of PKC-, antiviral CD8(+) T cells presented an unresponsive phenotype in vitro, which could be restored with exogenous IL-2 or by Toll-like receptor ligand-activated dendritic cells. In striking contrast, PKC- appeared to be superfluous for in vivo antiviral responses irrespective of whether the virus infected systemically, was localized to the lung, or did not replicate. In addition, CD8(+) CCR7-effector memory responses were normal in PKC--deficient mice, both in lymphoid and peripheral tissues. Our data show that increased activation signals delivered in vivo by highly activated dendritic cells, as present during viral infections, overcome the requirement for PKC- during CD8(+) T cell antiviral responses.